The Terrorist Experiences: Capturing Deradicalization and Counterterrorism in Indonesia - Erick, John (Indonesian Journal of Counter Terrorism and National Security, 2024)
This paper aims to delve into the nuanced and multifaceted realm of terrorism in Indonesia, focusing specifically on understanding the experiences of terrorists themselves, and the subsequent processes of deradicalization and counterterrorism within the country. Through a combination of qualitative research methods, including interviews, case studies, and analysis of extremist narratives, this study seeks to shed light on the motivations, pathways, and challenges associated with terrorism and its aftermath in Indonesia. The research will explore the ideological foundations of terrorism, examining how socio-political, economic, and religious factors contribute to radicalization. It will investigate the tactics used in recruitment and the evolving nature of extremist narratives in Indonesia. Additionally, the paper will assess the effectiveness of various counterterrorism strategies implemented by governmental and non-governmental entities, including law enforcement agencies and civil society organizations. Furthermore, the study will scrutinize the process of deradicalization, rehabilitation, and reintegration of former terrorists, evaluating the success of existing programs and identifying barriers to their implementation. It will also analyze the role of community engagement, religious leaders, and social support networks in preventing radicalization and promoting deradicalization efforts. By synthesizing empirical evidence and insights from Indonesia's context, this paper aims to contribute to the broader discourse on terrorism and counterterrorism strategies. It seeks to provide actionable recommendations for policymakers, practitioners, and researchers to enhance efforts in combating terrorism while fostering peace and resilience in Indonesia and beyond.Terrorism